Inhaled liposomal ciprofloxacin protects against a lethal infection in a murine model of pneumonic plague - Hamblin, Karleigh A.; Armstrong, Stuart J.; Barnes, Kay B.; Davies, Carwyn; Laws, Thomas R.; Blanchard, James D.; Harding, Sarah V.; Atkins, Helen S. (Frontiers in Microbiology, 2017)
Inhalation of Yersinia pestis can lead to pneumonic plague, which without treatment is inevitably fatal. Two novel formulations of liposome-encapsulated ciprofloxacin, ‘ciprofloxacin for inhalation’ (CFI, Lipoquin®) and ‘dual release ciprofloxacin for inhalation’ (DRCFI, Pulmaquin®) containing CFI and ciprofloxacin solution, are in development. These were evaluated as potential therapies for infection with Y. pestis. In a murine model of pneumonic plague, human-like doses of aerosolized CFI, aerosolized DRCFI or intraperitoneal (i.p.) ciprofloxacin were administered at 24 hours (representing prophylaxis) or 42 hours (representing treatment) post-challenge. All three therapies provided a high level of protection when administered 24 hours post-challenge. A single dose of CFI, but not DRCFI, significantly improved survival compared to a single dose of ciprofloxacin. Furthermore, single doses of CFI and DRCFI reduced bacterial burden in lungs and spleens to below the detectable limit at 60 hours post-challenge. When therapy was delayed until 42 hours post-challenge, a single dose of CFI or DRCFI offered minimal protection. However, single doses of CFI or DRCFI were able to significantly reduce the bacterial burden in the spleen compared to empty liposomes. A three-day treatment regimen of ciprofloxacin, CFI, or DRCFI resulted in high levels of protection (90% -100% survival). This study suggests that CFI and DRCFI may be useful therapies for Y. pestis infection, both as prophylaxis and for the treatment of plague.